Cancer-associated retinopathy: an autoimmune retinopathy - Tradjutrisno, Nurbuanto (Faculty of Medicine, Trisakti University, 2010)
Cancer-associated retinopathy (CAR) is a paraneoplastic syndrome most commonly associated with small-cell carcinoma of the lung, but also less frequently reported in patients with breast, endometrial, and other cancers. A paraneoplastic syndrome (PNS) is a secondary organ dysfunction occurring in a cancer patient at a site that is anatomically remote from the tumor. PNS is not due to a direct effect of the tumor itself or its metastases but caused by other mechanisms, commonly autoimmune mechanisms develop when malignant tumors express proteins, paraneoplastic antigens (PNA), which are normally present only in neurons. One retinal antigen implicated in the autoimmune mechanism of CAR is recoverin, a 23 kDa photoreceptor-specific calcium-binding protein modulating the activity of photoreceptor guanylyl cyclase. The anti-recoverin antibodies induced by the primary tumor may on contact with intraretinal recoverin initiate a photoreceptor degeneration and trigger photoreceptor death by apoptosis, thus causing blindness. Other circulating antibodies directed against a 46 kDa protein identified as retinol enolase and a 60 kDa retinal protein have been demonstrated in patients with clinically diagnosed CAR syndrome. In certain patients no specific antibody has been identified. This suggests that the CAR syndrome includes an heterogenous group of autoimmune conditions directed against various retinal proteins.